The Oil That Lasted a Thousand Years - Scolnic, Benjamin (Zutot, 2024)
Abstract While the familiar Hanukkah story of the ‘miracle of the oil’ is often dismissed as quaint and fanciful, it may be seen as a final link in an interesting chain of traditions about the sanctity of Judaism’s holiest of places. In the book of Exodus, one type of oil is used to light the lamps and another oil is used to anoint the Tabernacle and make it inviolate. The Tabernacle became part of the First Temple so there was no need to anoint the Holy of Holies there. In the time of the First Temple, some considered the Temple to be inviolate. When the First Temple was destroyed, no aspect of the new Temple was anointed. In the 160s BCE, during the Antiochene persecution, some felt the need to explain how the Temple could have been violated. The author of Daniel 9 reinterpreted Jeremiah’s prophecies of the 70 years of exile to be 70 weeks of years so that everything that had befallen the Judeans was seen as part of God’s overarching plan. The complex issues of continuity/discontinuity between, and the violability/inviolability of the temples, underlie Dan. 9 and related texts.
Keywords: Book of Daniel; Hanukkah; Jeremian prophecies; continuity/discontinuity; dept.jst; oil; peer-reviewed; temples

The failure of Poseidon, 'Averter of Disaster' and the mythical geography of Isaiah 23:1-14 - Scolnic, B. (Acta Antiqua Academiae Scientiarum Hungaricae, 2024)
The nostos, the return home in Greek mythology, is most often a journey over the sea, and it is the god Poseidon who rules the sea, both ensuring the safe passage of fishermen and sailors and causing disasters to individuals like Ajax son of Oileus, sometimes through obstacles like his daughter Charybdis. Most famously, he uses his power to hinder the nostos of Odysseus, all the while knowing he cannot prevent him from reaching home. This example illustrates how a god who may once have been the most powerful deity can no longer control ultimate results. As his power declines over the centuries, that of Zeus increases. It is also by sea that we see the ships in Isaiah 23, attempting to return to their homes in Sidon and Tyre on the eastern Mediterranean coast. In this Biblical passage from the eighth century BCE, the ships wail when they see that their seaport homes have been destroyed; there are no homes to which they can return. The great god of the Sea and the epichoric gods have failed to protect the cities which are considered their progeny. The Israelite prophet mocks their powerlessness and celebrates the power of his One God. There is no nostos, no homecoming for ships because they no longer have homes. Just as Poseidon could not prevent Odysseus from his nostos, the so-called Averter of Disaster has not prevented the disaster that has befallen his children. © 2023 Akadémiai Kiadó, Budapest.
Keywords: Biblical-Mythological Inter-Connections; Odyssey; Poseidon; dept.jst; nostos; peer-reviewed